2012
DOI: 10.1115/1.4007589
|View full text |Cite
|
Sign up to set email alerts
|

Stability Limits of Reversible-Pump Turbines in Turbine Mode of Operation and Measurements of Unstable Characteristics

Abstract: Measurements have been performed on a reversible-pump turbine model installed in a closed loop conduit system. The characteristics of the unstable pump turbine in turbine mode show a hysteresis pattern. Hence the output of the system is dependent on the previous state of the flow and not only the input variables. The hysteresis pattern is a characteristic of the whole system, but is caused by the unstable pump turbine. The unstable part of the characteristics was measured by three different methods: 1) by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…Zhu et al [40] Model pump-turbine (corresponding prototype Hr ¼ 259m, Pr ¼ 255MW) Negative blade lean lead to a weaker S-shaped characteristic Nielsen et al [36] and Olimstad et al [37,38] (ns ¼ 114) Low-specific-speed model pump-turbine…”
Section: Pump-turbine Geometric Parameters Examined With Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al [40] Model pump-turbine (corresponding prototype Hr ¼ 259m, Pr ¼ 255MW) Negative blade lean lead to a weaker S-shaped characteristic Nielsen et al [36] and Olimstad et al [37,38] (ns ¼ 114) Low-specific-speed model pump-turbine…”
Section: Pump-turbine Geometric Parameters Examined With Resultsmentioning
confidence: 99%
“…[36]. [37,38] on the runner geometry effect on the S-shaped characteristics. They observed that there is a major influence on the steepness characteristics by the diameter and speed of rotation.…”
Section: Pump-turbine Geometric Parameters Examined With Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Static tests of pump turbines [1,2] and computational fluid dynamics numerical methods [3,4] can reveal the complex hydraulic phenomena of the internal runner when a pump turbine is operating in the S region, such as stationary vortices, unsteady vortex, and the rotating stall that results in the blockage effect; all these phenomena are fundamental causes for the inversion of the S-shaped characteristic curve. Moreover, the S-shaped characteristics also lead to unstable runaway or no-load operations [5][6][7][8], as well as water-hammer pressure surge after load rejections.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the S-shaped characteristics, the dynamic processes of a pumped storage station is complicated: 1) The unstable pump turbine S-shaped characteristics make it difficult to measure the Sshaped curves, which can, therefore, be obtained by the transient method [9,10]; 2) pump turbines often show an unstable runaway and no-load operations, which are close to the form of S-shaped curves [5][6][7][8]; 3) in the load rejection process, the water-hammer pressure is also related to the Sshaped curves; 4) in some extreme conditions, such as OAA load rejections, numerical simulations have shown that the water-hammer pressure, especially in the draft tube, is fairly significant [11,12]; 5) to control the water-hammer pressure and runaway speed during the load rejection process, multiphase closing schemes can be used to guarantee the safety of a pumped storage station [13]. Therefore, based on the transient issues described above, the relevant verification experiments were conducted to clarify the effects of S-shaped characteristics on hydraulic transients.…”
Section: Introductionmentioning
confidence: 99%